Imidazoles as Serotonin Receptor Modulators for Treatment of Depression: Structural Insights and Structure-Activity Relationship Studies - Kapil Kumar Goel; Somesh Thapliyal; Rajeev Kharb; Gaurav Joshi; Arvind Negi; Bhupinder Kumar (MDPI AG, 2023)
Serotoninergic signaling is identified as a crucial player in psychiatric disorders (notably depression), presenting it as a significant therapeutic target for treating such conditions. Inhibitors of serotoninergic signaling (especially selective serotonin reuptake inhibitors (SSRI) or serotonin and norepinephrine reuptake inhibitors (SNRI)) are prominently selected as first-line therapy for the treatment of depression, which benefits via increasing low serotonin levels and norepinephrine by blocking serotonin/norepinephrine reuptake and thereby increasing activity. While developing newer heterocyclic scaffolds to target/modulate the serotonergic systems, imidazole-bearing pharmacophores have emerged. The imidazole-derived pharmacophore already demonstrated unique structural characteristics and an electron-rich environment, ultimately resulting in a diverse range of bioactivities. Therefore, the current manuscript discloses such a specific modification and structural activity relationship (SAR) of attempted derivatization in terms of the serotonergic efficacy of the resultant inhibitor. We also featured a landscape of imidazole-based development, focusing on SAR studies against the serotoninergic system to target depression. This study covers the recent advancements in synthetic methodologies for imidazole derivatives and the development of new molecules having antidepressant activity via modulating serotonergic systems, along with their SAR studies. The focus of the study is to provide structural insights into imidazole-based derivatives as serotonergic system modulators for the treatment of depression.